Effects of perceived service quality, website quality, and reputation on purchase intention: The mediating and moderating roles of trust and perceived risk in online shopping - Sikandar Ali Qalati (Taylor & Francis Group, 2021)
This paper aims to investigate the relationship between antecedents of trust in online shopping and purchase intention. Specifically, it examines the relationship between perceived service quality, perceived website quality, and perceived reputation, as well as the mediating role of trust in online shopping and the moderating role of perceived risk between trust and online purchase intention. An online survey was used to collect data (356 valid responses) and SmartPLS structural equation modelling (PLS-SEM) was employed to hypothesize a model. Data were collected from September to December 2019. Results suggest the moderating role of perceived risk over trust in online shopping and purchase intention. The slope for the relationship between trust in online shopping and purchase intention is moderated by perceived risk, showing that the relationship becomes stronger when perceived risk is high. Trust significantly mediates the relationship between perceived service quality, website quality reputation, and online purchase intention. This work furthers web-store decision makers’ understanding of the significant influence of trust and its mediating impact on online shopping and demonstrates how an increase in trust decreases the intensity of the impact of perceived risk on online purchase intention. To increase the number of sales and decrease the intensity of risk, companies must increase the level of trust, which mitigates risk and increases customer bonding with companies. As there is no consensus on the mediating role of trust in online shopping and the moderating role of perceived risk, this paper aims to fill this gap in the literature.